Association of toxoplasmosis with risk factors among adults in Duhok Province, Kurdistan Region, Iraq - Mustafa Riadh Hussein; Wijdam Mero (Faculty of Medicine, Universitas Trisakti, 2026)
BACKGROUNDToxoplasma gondii is a widespread zoonotic parasite that infects approximately one-third of the global population. Humans become infected mainly by consumption of undercooked meat or water or fruits and vegetables contaminated with oocysts. This study aimed to investigate the seroprevalence of toxoplasmosis and associated risk factors in adults from Duhok province, Iraq. MethodsA cross-sectional study was conducted with 600 participants (ages 22–60 years, both genders) from Duhok. Variables included age, gender, occupation, interaction with cats, and hygiene practices were collected. Blood samples were analyzed for anti-Toxoplasma IgM and IgG antibodies, using ELISA. Multiple logistic regressions were used to identify risk factors for toxoplasmosis. ResultsThe overall seroprevalence was 39.17% (IgG: 31.67%, IgM: 7.5%). Both IgM and IgG prevalence were significantly associated with gender (p<0.001). IgG was more prevalent in participants aged 31–40 years (p<0.001). Key risk factors included cat contact (aOR=4.50, 95% C.I.: [2.10, 9.50], p<0.001), drinking tap water (aOR=3.00, 95% C.I.: [1.50, 6.00], p=0.005), consuming undercooked meat (aOR=3.20, 95% C.I.: [2.00, 5.30], p<0.001), eating unwashed vegetables (aOR=2.50, 95% C.I.: [1.50, 4.30], p<0.001), eating outside home (aOR=2.50, 95% C.I.: [1.50, 4.00], p<0.001), and a history of arthritis (aOR=3.00, 95% C.I.: [2.00, 4.50], p<0.001), hygiene practices, such as handwashing (aOR=0.30, 95% C.I.: [0.15, 0.60], p=0.001) and hygienic measures (aOR=0.35, 95% C.I.: [0.20, 0.60], p<0.001), reduced risk former Covid-19 (aOR=7.00, 95% C.I.: [3.50, 14.00], p<0.001). ConclusionsToxoplasmosis in Duhok is associated with dietary habits, sanitation, and cat contact. Enhancing hygiene and food safety can reduce the disease burden, particularly in immunocompromised individuals.